Exploring the relationship between healthcare expenditure, income, medical technology, and aging: A pooled mean group analysis of African countries - Houeninvo, Hilaire Gbodja; Assouto, Achille Barnabe (Asian Journal of Economic Modelling, 2023)
This paper empirically examines the short and long-run relationships among healthcare expenditure, income, medical technology, and an aging population in a panel of 45 African countries over the period 1995-2018. We test for cross-sectional dependence among different countries and employ the pooled mean group estimator. The results support the presence of cross-sectional dependence in African countries and reveal that healthcare expenditure, income, medical technology, and aging population have a long-run relationship. Medical technology and an aging population are key drivers of healthcare expenditure in the low-income group as well as the middle-income group. The long-run income elasticities of healthcare expenditure are less than one for both income groups. Finally, we found bidirectional causality between healthcare expenditure and its determinants. Healthcare expenditure is considered a necessity for African countries. Nevertheless, low-income countries have higher income elasticities for private health expenditure compared to middle-income countries. We suggest that African governments should increase public healthcare spending since healthcare spending is a necessity. This increase will lead to growth in income and medical technology development, which will have a beneficial impact on health status.